A comparative investigation of the opaqueness of human capital information in China and the United Kingdom - Wang, Xingchen (2022)
Although human capital has long been viewed as a critical asset of a business, there are no clear international criteria for its disclosure. High-quality human capital reporting quality is in line with social expectations. However, some companies will also use the disclosure of human capital report as a means of corporate image management. In the extant literature, few scholars have studied the differences between the disclosure of human capital in developed and developing countries. Taking 2018 as the research period, this paper adopts the content analysis method to study the annual reports of 25 largest British companies and 25 largest Chinese companies to discover the different tendencies of Chinese and British companies to disclose human capital information. The findings indicate that Chinese corporations' human capital reporting quality is superior to that of British enterprises. Chinese companies tend to use numerical information when disclosing human capital, while British companies tend to use narrative information. This study provides further evidence for the different tendencies of disclosure of human capital in developing and developed countries. At the same time, it is beneficial to encourage companies to improve human capital reporting transparency.